Інтервальна модель портрету користувачів тематичної групи з проблем екології у соціальній мережі - Дивак, Микола Петрович; Мельник, Андрій Миколайович; Кедрін , Євген Станіславович; Otoo, Frank Avalon (Vinnytsia National Technical University, 2022)
Mathematical models of dynamics of efficiency of information social networks are considered in the work. An approach to estimating model parameters is proposed. A number of experimental studies were conducted on the basis of data on the functioning of a special online group Facebook. The indicator of the characteristics of the information message was studied. An interval discrete model in the form of a difference equation is obtained, which describes the dynamics of users' reactions to messages in thematic groups of social networks. On the basis of the conducted experiments, the efficiency of application of the offered model is confirmed